SUGARCANE GROWERS ATTITUDE TOWARDS SUGARCANE PRODUCTION AND MARKETING, DHARMAPURI DISTRICT, TAMILNADU, INDIA - Sakunthala, K.; Sakunthala, K.; Thanigasalam, G. (International Journal of Psychosocial Rehabilitation, 2020)
Agriculture is one of the most significant sectors of the Indian Economy. Nearly two thirds of the Indian workers are living with agriculture and allied activities. In India number of crops grown by farmers such as different food crops, commercial crops, oil seeds etc. Sugarcane is one of the important commercial crops grown in India. The objectives of the study are to know the Demographic profile sample farmers and to study the Sugarcane Growers Attitude about Production and Marketing of Sugarcane in sample Dharmapuri district. The multi-stage random sampling technique was adopted. The total of 30 village panchayats and 150 sugarcane growers were determined as the sample of the study. From the analysis result the study found that most of the sample farmers were comes under the age group of 31-50, majority of the sample sugarcane growers were male and completed a higher secondary and degree level education, majority of the sample sugarcane growers are doing sugarcane cultivation is the primary occupation and earned Rs.25001-50000 per annum from sugarcane production. Further the analysis of cultivation variables reveals that majority of the sample respondents have cultivating 1-5 acres and 6-10 years experience in sugarcane production. The attitude about production, harvesting, marketing and financial aspects reveals that majority of the sugarcane growers in sample Dharmapuri district were not satisfied about the production, harvesting, marketing and financial aspects except soil fertility, labour available for production and manure available in private market.